Evaluation of bacterial contamination of miswak toothbrushes in different storage environments: An experimental study (Annals of Medical Research, 2024)
Aim: To evaluate the microorganism levels on miswak toothbrushes and to investigate the effect of storage conditions.Materials and Methods: 24 Participants kept miswak toothbrushes in the bathroom and room for one month. Thioglycolate was left in the liquids by cutting 1/3 of the miswak hairs, and incubation was provided for microorganisms. Precise identification of microorganisms is achieved with VITEK® 2 Compact. The periodontal health of the participants was evaluated at the beginning and end of the study by evaluating the bleeding on their plaque, gingival indices, sulcus depths, and probing values.Results: Seventeen (70.80%) participants were female and 7 (29.20%) were male. Half of the participants kept their toothbrushes in the bathroom, and the other half in their room. Lactobacillus spp. was found in 29.2% of toothbrushes, with an average count of 2.43±1.71x102 CFU/ml. Streptococcus mutans were found in 88.3% of toothbrushes, with an average count of 4.05±1.64x102 CFU/ml. Of the toothbrushes tested, 25.0% had Candida albicans present with an average count of 3.18±1.47x102 CFU/ml. Lactobacillus spp. in 29.90% of Miswak toothbrushes, S. mutans was found in 83.30% and C. albicans in 25%. No significant difference was observed in periodontal index values.Conclusion: 84% of miswak toothbrushes are contaminated with persistent bacteria in the first month of use, regardless of storage method. Storing miswak toothbrushes in a humid environment results in higher rates of S. mutans bacterial contamination and survival. Surprisingly, colonization and survival of Lactobacillus spp. and C. albicans were higher in miswak toothbrushes stored at room temperature. It should be replaced with miswak toothbrushes every month instead of the previously suggested three months.
Keywords: Miswak; Contamined toothbrush; Toothbrush storage; Toothbrush plastic cover; Streptococcus mutans